Evaluation of the Health Impact of the National Diabetes Program in Paraguay - Rodríguez, Patricia Vera (2021)
The clinical evolution of a diabetic patient is linked to its compliance with nonpharmacological measures such as diet, physical activity, acquiring habits, medical controls and also with its pharmacological treatment. In different Latin American countries such as the Republic of Paraguay, there are National Programs to provide free support and treatment to the diabetic population that mostly have vulnerable social conditions. However, the impact of these government policies is not routinely evaluated. In order to establish the achievements of a state diabetes program, the present study was carried out. Methodology: This is a descriptive, cross-sectional study with an analytical stage. Results: low adherence to non-pharmacological measures such as diet and physical activity was detected. A high percentage of patients were overweight (38%) or obese (46.5%). 75% of the population enrolled in this study did not comply with the program recommendations regarding the time and frequency of physical activities, nor they complied with the minimum 6 daily meals required. Only 37% of the patients had normal levels of glycated hemoglobin and 51.3% of them had pharmacological treatment adherence. Low compliance was observed in relation to regular medical examinations (which were under free coverage by the program) that are transposed in 22% of retinal studies and 60% in 24-hour urine analysis for the early detection of complications such as retinopathy and nephropathy. Conclusion: Despite the economic and logistical efforts carried out by State programs in order to care of people with diabetes mellitus, data showed a low adherence of patients to the proposed pharmacological and non-pharmacological measures. A personalized follow-up strategy is necessary to improve treatment adherence and to obtain better therapeutic results.